Pelanggaran Etik Profesi Advokat Pada Tindak Premanisme di Persidangan Dalam Perspektif Hukum dan Etika Profesi - Azahra, Musdalifah; Lewoleba, Kayus Kayowuan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the legal and professional ethics perspectives on acts of thuggery committed by advocates in court and efforts to enforce the code of ethics of the profession to prevent and handle violations of ethical discipline. The research method used is normative juridical with a qualitative approach, through doctrinal studies of laws and regulations, advocate codes of ethics, court decisions, and related literature such as books, journals, and legal articles. This study also analyzes real case examples, namely ethical violations committed by the Razman Arif Nasution advocate team in a feud with Hotman Paris Hutapea at the North Jakarta District Court, which involved acts of thuggery in court. The results of the study indicate that violations of advocate ethics, including acts of thuggery in court, not only damage the integrity of the legal profession but also disrupt the justice system and public trust. Enforcement of the advocate code of ethics plays a crucial role in maintaining the dignity of the profession as (officium nobile). Cases such as the violation committed by Firdaus Oiwobo prove that without supervision and strict sanctions, the advocate profession can lose its authority. Therefore, every violation must be followed up through the mechanism regulated in the Indonesian Advocate Code of Ethics, which allows the public, clients, colleagues, and professional institutions to report violations in writing.